Adobe Dreamweaver CS3 Revealed - Sherry Bishop (Cengage Learning, Inc, 2008)
Whether you're looking for a step-by-step guide to introduce you to Adobe Dreamweaver CS3 or a solid reference to assist you as you continue your work in web design, this is the resource you've been looking for! Adobe Dreamweaver CS3 Revealed uses detailed, vibrant illustrations, clear, straightforward lessons, and real-world case studies to provide an overview of the Dreamweaver interface and how to use it effectively. This latest edition includes expanded content on using CSS, inserting video files, using Adobe Bridge CS3, conducting browser compatibility checks and more, reflecting the most recent updates to the Dreamweaver software, as well as those that have occurred in the larger environment of web design. Sidebars throughout the book incorporate basic web design principles, providing readers with a skill set that goes beyond the software interface and can be applied in a variety of situations